Efficacy and safety of oral sildenafil in treatment of pediatric head and neck lymphatic malformations. (3rd June 2017) - Wang, Shengcai; Zhang, Jie; Ge, Wentong; Liu, Yuanhu; Guo, Yongli; Liu, Yue; Wang, Ning; He, Yuzhu; Tai, Jun; Ni, Xin
Abstract: Conclusions: Low dose oral sildenafil citrate tablets are safe and effective to decrease the lesions volume in some LMs children, especially with macrocystic lesion or mixed type. Objective: To evaluate the efficacy and safety of oral sildenafil in treatment of pediatric head and neck lymphatic malformations (LMs). Subjects and methods: In this open-label study, 21 children diagnosed with LMs were given oral sildenafil and stopped at week 24. Volume change of lesions compared with baseline was used to evaluate therapeutic outcome. The improvement of various symptoms and the adverse effects of sildenafil were recorded during the follow-up period. Results: Eight patients (38.0%) showed excellent improvement (>75–100%), one patient (4.8%) had good (>50–75%), two patients (9.6%) had fair (>25–50%), three patients (14.3%) had minimal (0–25%), and seven patients (33.3%) had no improvement. The snoring or stridor completely disappeared in two subjects, although there was no apparent decrease in LMs size. Moreover, all three patients with macrocystic lesions displayed a positive response to sildenafil treatment, followed by mixed type (9/12, 75%). Only two out of six patients with microcystic lesions had minimal clearance. Only four patients showed transient mild diarrhea, there was no other adverse effect in this series.